Effects of Acremonium terricola Culture on Lactation Performance, Immune Function, Antioxidant Capacity, and Intestinal Flora of Sows - Zhirong Chen; Lixia Xiao; Qian Sun; Qiangqiang Chen; Weidong Hua; Jinzhi Zhang (MDPI AG, 2024)
This study aimed to determine the effects of different doses of Acremonium terricola culture (ATC) on lactation performance, immune function, antioxidant capacity, and intestinal flora of sows. Forty-five Landrace sows (3-6 parity) were randomly assigned to the following three treatments from 85 days of gestation to 21 days after farrowing: a control diet (CON, basal diet), a low-dose Acremonium terricola culture diet (0.2% ATC, basal diet + 0.2% ATC), and a high-dose Acremonium terricola culture diet (0.4% ATC, basal diet + 0.4% ATC). Compared with the CON group, the supplementation of 0.2% ATC increased the average daily milk yield of sows by 4.98%, increased milk fat, total solids, and freezing point depression on day 1 postpartum (p < 0.05), increased serum concentration of Triiodothyronine, Thyroxin, and Estradiol on day 21 postpartum (p < 0.05). Compared with the CON group, the supplementation of 0.4% ATC increased the average daily milk yield of sows by 9.38% (p < 0.05). Furthermore, the supplementation of 0.2% ATC increased serum concentration of IgG, IgM, and IFN-γ, CD4 on day 1 postpartum (p < 0.05) and increased serum concentration of immunoglobulin A ( IgA), immunoglobulin G (IgG), immunoglobulin M ( IgM), complement 3 (C3), cluster of differentiation 4 (CD4), cluster of differentiation 8 (CD8), interferon-γ (IFN-γ) on day 21 postpartum (p < 0.05), while the supplementation of 0.4% ATC reduced serum concentration of IL-2 on day 21 postpartum (p < 0.05). Moreover, the supplementation of 0.4% ATC significantly increased serum concentration of catalase (CAT) (p < 0.05). Additionally, the supplementation of ATC affected the relative abundance of the intestinal flora at different taxonomic levels in sows and increased the abundance of beneficial bacteria such as in the norank_f__Eubacterium_coprostanoligenes group, Eubacterium_coprostanoligenes group, and Lachnospiraceae_XPB1014 group of sows, while reducing the abundance of harmful bacteria such as Phascolarctobacterium and Clostridium_sensu_stricto_1. These data revealed that the supplementation of ATC during late gestation and lactation can improve lactation performance, immune function, antioxidant capacity, and the gut microbiota. Compared with supplementation of 0.4% ATC, 0.2% ATC enhances the levels of thyroid-related hormones, specific antibodies, and cytokines in serum, promotes the diversity of beneficial gut microbiota, beneficial bacteria in the intestine, reduces the population of harmful bacteria, and thereby bolsters the immunity of sows. Hence, 0.2% ATC is deemed a more optimal concentration.